1996
DOI: 10.1161/01.cir.93.9.1640
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Depletion Attenuates Reperfusion Injury in Patients With Left Ventricular Hypertrophy

Abstract: These results demonstrate that leukocyte-depleted reperfusion is potentially beneficial as an adjunct to terminal cardioplegia during cardiac surgery to attenuate reperfusion injury in patients with left ventricular hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 26 publications
2
56
0
1
Order By: Relevance
“…Although the leukocyte contribution to myocardial reperfusion injury has been demonstrated 13,[15][16][17][18][19] and discussed 20 before, only have recent studies revealed an interaction between the leukocyte and platelet compartments as effectors of reperfusion injury. 8,21,22 In particular, the study of Lefer and coworkers 8 suggested that blockade of P-selectin and its ligands, eg, PSGL-1, reduced PMN-platelet-dependent myocardial reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although the leukocyte contribution to myocardial reperfusion injury has been demonstrated 13,[15][16][17][18][19] and discussed 20 before, only have recent studies revealed an interaction between the leukocyte and platelet compartments as effectors of reperfusion injury. 8,21,22 In particular, the study of Lefer and coworkers 8 suggested that blockade of P-selectin and its ligands, eg, PSGL-1, reduced PMN-platelet-dependent myocardial reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…injury to a number of organs, including the heart, liver, and lung, and is thought to also contribute to the pathogenesis of chronic diseases associated with cell death (5,31,32). Therefore, it could potentially be of therapeutic benefit to block this sterile inflammatory response.…”
Section: Figurementioning
confidence: 99%
“…They also help to clear dead cells and debris and stimulate mechanisms to repair tissue damage. On the other hand, recruiting the innate defenses comes at a price (4)(5)(6). The delivery of the immune effector mechanisms is imprecise, and as a result, normal healthy cells may be caught in the line of fire and damaged.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that patients with more than one risk factor for atherothrombosis have a smoldering inflammatory response that could have a detrimental effect on the host. These data are relevant in the era in which antileukocyte therapeutic interventions are considered [8, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%